Induction of apoptosis by an oleanolic acid derivative in SMMC-7721 human hepatocellular carcinoma cells is associated with mitochondrial dysfunction - Fan, Xinfeng (Oncol Lett, 2018)
The aim of the present study was to investigate the effects of an oleanolic acid derivative, a novel antitumor drug, on the growth of SMMC-7721 human hepatocellular carcinoma cells and the underlying mechanism. An MTT assay was performed to determine the cytotoxicity of the oleanolic acid derivative. Cell membrane integrity was assessed using fluorescence microscopy to assess the uptake of annexin V-FITC/propidium iodide (PI). Western blotting was used to detect the apoptosis-associated proteins B cell lymphoma-2 (Bcl-2), Bax, caspase-9 and caspase-3. A spectrophotometer was used to analyze the intracellular adenosine triphosphate (ATP) expression level. The loss of mitochondrial membrane potential was detected by performing the JC-1 assay. ELISA was used to evaluate the content of cytochrome c (Cyt-C). The oleanolic acid derivative reduced the cell viability of SMMC-7721 cells in a dose- and time-dependent manner. The half maximal inhibitory concentration values of the oleanolic acid derivative in SMMC-7721 cells at 24, 48 and 72 h were 26.80, 11.85, and 6.66 µM, respectively. The antiapoptotic-protein Bcl-2 was downregulated, and the proapoptotic protein Bax was upregulated following treatment with the oleanolic acid derivative for 48 h. The oleanolic acid derivative induced the cleavage of caspase-9 and caspase-3 as well as promoted annexin V-FITC/PI uptake in SMMC-7721 cells. Furthermore, treatment of SMMC-7721 cells with the oleanolic acid derivative induced a reduction of the intracellular ATP expression level, loss of ΔΨm and Cyt-C release from the mitochondria. The oleanolic acid derivative induced apoptosis in SMMC-7721 human cells. Mitochondrial dysfunction was involved in the anticancer effects of this derivative on SMMC-7721 human cells.